Anchorage Performance of Headed Reinforcement Bar Embedded in Roof Exterior Beam-Column Joints - Zev Al Jauhari; Tomoya Matsui (Civil Engineering Journal, 2026)
The anchorage behavior of headed reinforcement bars embedded in roof exterior beam–column joints is influenced by the presence and configuration of supplementary reinforcement bars. This study aims to develop an improved predictive formulation for anchorage capacity by introducing a modification factor that accounts for the effect of supplementary bars through a combined numerical and analytical approach. A three-dimensional nonlinear FE model was developed and validated against previously reported pullout test results for load–displacement response, crack propagation, reinforcement strain behavior, and stress distribution. The numerical results showed agreement with experimental observations and accurately captured the failure modes. To further interpret the internal force mechanism, a three-dimensional strut-and-tie model (STM) was formulated based on principal stress trajectories obtained from FE analysis. The proposed STM successfully predicted the anchorage capacity, consistent with the experimental results. Parametric studies revealed that increasing the supplementary bar ratio significantly enhances pullout capacity by enlarging the compression strut area and improving confinement within the joint region. Based on regression analysis of the STM results, a new coefficient was introduced to refine the modified Kubota and Murakami empirical formula, incorporating the effect of supplementary bar ratio. The revised formulation provides improved prediction accuracy with low statistical dispersion.